Analisis kelayakan teknis dan finansial pendirian usaha pengolahan sabut dan tempurung kelapa di Kecamatan Pengabuan Kabupaten Tanjung Jabung Barat Provinsi Jambi - Ade Yulia; Lisani Lisani (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
The productivity of coconuts produced by Pengabuan sub-district is 14,481 tons of coconuts/year. Coconut processing only focuses on the fruit meat which is processed into copra. Copra processing produces by-products namely coconut husks and shells that have not been used optimally. Coconut husk and shells can be processed into bio briquettes. This study aims to analyze the technical and financial feasibility of the plan to establish coconut husks and shells processing business into bio briquettes in Pengabuan Subdistrict, West Tanjung Jabung District, Jambi Province. The research method used is quantitative and qualitative study. The results showed that this business plan required 1,197 tons of coconut husk per year and 1,064 tons of coconut shell per year. One production time requires 997.5 kg of coconut husk charcoal and 665 kg of coconut shell charcoal and 87.5 kg of tapioca flour. The characteristics of the bio briquettes produced were water content of 5.73 %, yield of 73 % by weight of charcoal flour, flame duration test of 284.3 seconds, burning time of 96 minutes and burning rate of 0.1598 grams / minute. The location chosen to set up this business is Parit Pudin Village. The type of layout used is the product type with the material flow pattern is the U type. The feasibility of the financial aspect includes an NPV of 2,169,282,959, an IRR of 59.42 %, a payback period of 4.66 years, net B/C of 1.18. Overall technical and financial feasibility criteria found that the biobriquette business from husk and coconut shells is feasible to establish